Complications of open wedge high tibial osteotomy. Analysis of the causes of complications and ways to eliminate them - V. E. Bialik; S. A. Makarov; E. I. Bialik; V. A. Nesterenko; M. R. Nurmukhametov (Научно-практическая ревматология)
Objective – to study the complications of open wedge high tibial osteotomy (OWHTO) in patients who underwent this surgery in the V.A. Nasonova Research Institute of Rheumatology.Materials and methods. The study included 43 patients (46 knee joints) with primary and secondary OA of the knee of I–III stages, who underwent OWHTO in the period from 2005 to 2019. The operation was performed according to the standard technique using short spacer plates (Puddu I (5 times) and II generation (24 times), Osteomed (17 times)) and bone grafting. The identified OWHTO specific complications were divided into those related to the osteotomy, fixation, and bone grafting. To assess the result, we studied the change in pain according to the Visual Analog Scale (VAS), as well as the functional and objective state of the knee according to the Knee Society Score (KSS) before surgery, after 3 months and 1 year after surgery.Results. In 15 (32.7%) cases have been diagnosed 26 complications. Of these, 21 (81.0%) were associated with fixation, 2 (7.7%) with the osteotomy 2 (7.7%) with bone grafting of the osteotomy gap, and 1 (3.6%) a local complication. Patients without complications had a statistically significantly better decrease in pain intensity according to VAS (p=0.0005), and an improvement in the total score of KSS (p=0.0023) one year after surgery. Outcomes were also better in patients without complications: 96.7% excellent and good results versus 60.0% in patients with complications one year after OWHTO. In total, we had 43.5% excellent, 41.3% good and 15.2% satisfactory results one year after surgery.Conclusions. OWHTO is a highly effective method of surgical treatment of the osteoarthritis of the knee, which allows to obtain an excellent and good treatment result in 84.8% of cases one year after surgery. Performing OWHTO with fixing the height of the osteotomy gap using short spacer plates and bone grafting in 32.7% of cases is associated with the development of complications. To improve the results of OWHTO, it is necessary to improve the surgical technique and fixator.